Respuesta :

Answer:

Step-by-step explanation:

3x²=15-4x

divide by 3 on both sides

x²=5-[tex]\frac{4}{3}[/tex]x ​ ​

move everything to one side

x²+[tex]\frac{4}{3}[/tex]x ​-5 = 0

add the square of 1/2 the middle term of [tex]\frac{4}{3}[/tex]  but also subtract it too

x²+[tex]\frac{4}{3}[/tex]x +[tex]( \frac{2}{3} )^{2}[/tex]​-5-[tex]( \frac{2}{3} )^{2}[/tex]​ = 0

now use the property of a perfect square to rewrite

[tex](x+\frac{2}{3}) ^{2}[/tex] -5 -[tex]\frac{4}{9}[/tex] = 0

rewrite 5 as a fraction

[tex](x+\frac{2}{3}) ^{2}[/tex] - [tex]\frac{45}{9}[/tex]- [tex]\frac{4}{9}[/tex] = 0

add up the fractions

[tex](x+\frac{2}{3}) ^{2}[/tex] - [tex]\frac{49}{9}[/tex] = 0

move to the other side

[tex](x+\frac{2}{3}) ^{2}[/tex] = [tex]\frac{49}{9}[/tex]

take the square root of both sides :P

[tex]\sqrt{((x+\frac{2}{3}) ^{2} }[/tex]  = [tex]\sqrt{\frac{49}{9} }[/tex]

much easier looking now, just use algebra to solve for x

x + [tex]\frac{2}{3}[/tex] = [tex]\frac{7}{3}[/tex]

subtract  [tex]\frac{2}{3}[/tex]  from both sides

x + [tex]\frac{2}{3}[/tex] -  [tex]\frac{2}{3}[/tex] = [tex]\frac{7}{3}[/tex] - [tex]\frac{2}{3}[/tex]

x = [tex]\frac{5}{3}[/tex]

:)  

Answer:

x = - 3, x = [tex]\frac{5}{3}[/tex]

Step-by-step explanation:

Given

3x² =15 - 4x ( add 4x to both sides )

3x² + 4x = 15 ← factor out 3 from each term on the left side

3(x² + [tex]\frac{4}{3}[/tex] x) = 15

To complete the square

add/subtract ( half the coefficient of the x- term)² to x² + [tex]\frac{4}{3}[/tex] x

3(x² + 2([tex]\frac{2}{3}[/tex] )x + [tex]\frac{4}{9}[/tex] - [tex]\frac{4}{9}[/tex] ) = 15

3(x + [tex]\frac{2}{3}[/tex] )² - [tex]\frac{4}{3}[/tex] = 15 ( add [tex]\frac{4}{3}[/tex] to both sides )

3(x + [tex]\frac{2}{3}[/tex] )² = 15 + [tex]\frac{4}{3}[/tex] = [tex]\frac{49}{3}[/tex] ( divide both sides by 3 )

(x + [tex]\frac{2}{3}[/tex] )² = [tex]\frac{49}{9}[/tex] ( take the square root of both sides )

x + [tex]\frac{2}{3}[/tex] = ± [tex]\sqrt{\frac{49}{9} }[/tex] = ± [tex]\frac{7}{3}[/tex] ( subtract [tex]\frac{2}{3}[/tex] from both sides )

x = - [tex]\frac{2}{3}[/tex] ± [tex]\frac{7}{3}[/tex], then

x = - [tex]\frac{2}{3}[/tex] - [tex]\frac{7}{3}[/tex] = - 3

x = - [tex]\frac{2}{3}[/tex] + [tex]\frac{7}{3}[/tex] = [tex]\frac{5}{3}[/tex]